Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the equation of the tangent line to the circle [tex]\( x^2 + y^2 = 1 \)[/tex] at the point [tex]\( Q \left( \frac{1}{2}, \frac{\sqrt{3}}{2} \right) \)[/tex], we use the following method.
First, recall that the equation of the tangent to a circle [tex]\( x^2 + y^2 = r^2 \)[/tex] at a point [tex]\( (x_1, y_1) \)[/tex] on the circle is given by:
[tex]\[ x_1 x + y_1 y = r^2 \][/tex]
For our specific case, the circle has the equation [tex]\( x^2 + y^2 = 1 \)[/tex], meaning [tex]\( r^2 = 1 \)[/tex]. Thus, the tangent line at point [tex]\( Q \left( \frac{1}{2}, \frac{\sqrt{3}}{2} \right) \)[/tex] can be found using:
[tex]\[ \frac{1}{2} x + \frac{\sqrt{3}}{2} y = 1 \][/tex]
Next, we need to rearrange this equation into the slope-intercept form [tex]\( y = ax + b \)[/tex].
Starting from the tangent equation:
[tex]\[ \frac{1}{2} x + \frac{\sqrt{3}}{2} y = 1 \][/tex]
Isolate the [tex]\( y \)[/tex]-term:
[tex]\[ \frac{\sqrt{3}}{2} y = 1 - \frac{1}{2} x \][/tex]
Multiply both sides by [tex]\( \frac{2}{\sqrt{3}} \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2}{\sqrt{3}} - \frac{1}{\sqrt{3}} x \][/tex]
This simplifies to:
[tex]\[ y = \left( -\frac{1}{\sqrt{3}} \right) x + \frac{2}{\sqrt{3}} \][/tex]
Therefore, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] in the equation [tex]\( y = ax + b \)[/tex] are:
[tex]\[ a = -\frac{1}{\sqrt{3}} \approx -0.5773502691896258 \][/tex]
[tex]\[ b = \frac{2}{\sqrt{3}} \approx 1.1547005383792517 \][/tex]
Thus, the equation of the tangent line is:
[tex]\[ y = -0.5773502691896258 x + 1.1547005383792517 \][/tex]
So, the value of [tex]\( a \)[/tex] is [tex]\( -0.5773502691896258 \)[/tex] and the value of [tex]\( b \)[/tex] is [tex]\( 1.1547005383792517 \)[/tex].
First, recall that the equation of the tangent to a circle [tex]\( x^2 + y^2 = r^2 \)[/tex] at a point [tex]\( (x_1, y_1) \)[/tex] on the circle is given by:
[tex]\[ x_1 x + y_1 y = r^2 \][/tex]
For our specific case, the circle has the equation [tex]\( x^2 + y^2 = 1 \)[/tex], meaning [tex]\( r^2 = 1 \)[/tex]. Thus, the tangent line at point [tex]\( Q \left( \frac{1}{2}, \frac{\sqrt{3}}{2} \right) \)[/tex] can be found using:
[tex]\[ \frac{1}{2} x + \frac{\sqrt{3}}{2} y = 1 \][/tex]
Next, we need to rearrange this equation into the slope-intercept form [tex]\( y = ax + b \)[/tex].
Starting from the tangent equation:
[tex]\[ \frac{1}{2} x + \frac{\sqrt{3}}{2} y = 1 \][/tex]
Isolate the [tex]\( y \)[/tex]-term:
[tex]\[ \frac{\sqrt{3}}{2} y = 1 - \frac{1}{2} x \][/tex]
Multiply both sides by [tex]\( \frac{2}{\sqrt{3}} \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2}{\sqrt{3}} - \frac{1}{\sqrt{3}} x \][/tex]
This simplifies to:
[tex]\[ y = \left( -\frac{1}{\sqrt{3}} \right) x + \frac{2}{\sqrt{3}} \][/tex]
Therefore, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] in the equation [tex]\( y = ax + b \)[/tex] are:
[tex]\[ a = -\frac{1}{\sqrt{3}} \approx -0.5773502691896258 \][/tex]
[tex]\[ b = \frac{2}{\sqrt{3}} \approx 1.1547005383792517 \][/tex]
Thus, the equation of the tangent line is:
[tex]\[ y = -0.5773502691896258 x + 1.1547005383792517 \][/tex]
So, the value of [tex]\( a \)[/tex] is [tex]\( -0.5773502691896258 \)[/tex] and the value of [tex]\( b \)[/tex] is [tex]\( 1.1547005383792517 \)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.